Analysis Of Variation Of Paddle Wheel Photovoltaic Wheel Form In Microalgae Cultivation On Electricity Consumption - Naibaho, Winfrontstein; Welmar Olfan Basten Barat; Hiras Naibaho, Romson (International Journal of Science, Technology & Management, 2022)
The main problem that is often found in the failure of microalgae production is poor water quality during the maintenance period. One of the causes of deteriorating water quality is the lack of oxygen which endangers microalgae which can inhibit cell growth so that it can reduce its productivity. On this basis, efforts are needed to refresh the water or aeration to help increase the dissolved oxygen (DO) level in the microalgae growth container using a paddle wheel. The development of an aerator blade design that has optimum efficiency is needed to reduce high electricity consumption and see more effective cell growth. For these problems, in this study, variations of the paddle wheel will be analyzed. Variations in the shape of the wheel used, namely straight and curved with the available aerators, are expected to have an optimum speed, area coverage and increase the amount of dissolved oxygen (DO). The method used is the experimental method . Based on this research, it was found that an increase in the value of cell growth occurred in variations in the shape of a straight paddle wheel of 122 cells/ml .